2021
DOI: 10.3390/geriatrics6020040
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Applications Designed to Improve Older People’s Chronic Pain Management: An Integrated Systematic Review

Abstract: (1) Background: Older people’s chronic pain is often not well managed because of fears of side-effects and under-reporting. Telehealth interventions, in the form of smartphone applications, are attracting much interest in the management of chronic diseases, with new and evolving approaches in response to current population demographics. However, the extent to which telehealth interventions may be used to promote and effect the self-management of chronic pain is not established. (2) Aim: To provide an objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 67 publications
(138 reference statements)
1
14
0
2
Order By: Relevance
“…Our methods led to an acceptable recruitment rate with approximately three-quarters of eligible individuals enrolling in the study, which supports prior research showing that older adults with pain are interested in digital applications ( 8 , 9 , 38 ). Despite this success, the ability to retain participants was much lower than anticipated as evidenced by a dropout rate of 35%.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our methods led to an acceptable recruitment rate with approximately three-quarters of eligible individuals enrolling in the study, which supports prior research showing that older adults with pain are interested in digital applications ( 8 , 9 , 38 ). Despite this success, the ability to retain participants was much lower than anticipated as evidenced by a dropout rate of 35%.…”
Section: Discussionsupporting
confidence: 77%
“…Although the scope of mHealth applications and tools continues to expand, research examining the feasibility and efficacy of these technologies as a means of mitigating CNCP in older adults remains limited. One systematic review examined the effects of mHealth interventions on the management of CNCP in older adults and identified just 10 studies ( 9 ). The studies were largely qualitative, and the authors concluded that research investigating mHealth tools to manage CNCP in older adults remains scant ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informed by a recent review of the literature ( 11 ) and the findings of Wethington's 2018 consensus workshop, the project team developed a semi-structured topic guide to explore the dimensions of experience and engagement with technology. The guide was used to inform the development of an interview protocol ( Box 1 ) to conduct the focus groups.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research on the assessment and management of chronic pain has largely excluded older people and is dominated by pharmaceutical approaches ( 9 , 10 ). There is limited exploration of what technology means in terms of practical application, acceptability and feasibility for an ageing population ( 11 ). More specifically, the older person's own understandings and perceptions of the issue are marginalised in the literature.…”
Section: Introductionmentioning
confidence: 99%